PEMANFAATAN TUMBUHAN BAMBU DI KELURAHAN COBODOE KOTA TIDORE KEPULAUAN - Nurhafni A. Gafar; Abdulrasyid Tolangara; Nurmaya Papuangan (UNIVERSITAS KHAIRUN, 2022)
Bamboo is a versatile plant and occupies a special place in the life of Indonesian people. Bamboo is also a fairly available and inexpensive raw material for making household appliances and furniture, building materials, pipes for water distribution, musical instruments and religious purposes. In addition, some types of bamboo are ornamental plants and waste filter processors and erosion prevention. Bamboo belongs to the results of non-timber forests and can be used as an alternative to wood. This research aims to find out the form of utilization of bamboo plants in Cobodoe Village, East Tidore Subdistrict. This research is a descriptive study, with survey methods used to describe the diversity and form of utilization of bamboo plants in Cobodoe Village, East Tidore District. The results of this study found three types of bamboo, namely bambu tutul (Bambusa maculate), bambu tui (Schizostachyum lima), and bambu pagar (Bambusa glaucescens). People in Cobodoe Village use bamboo plants as raw materials for food and household furniture.